Nuclear industry family study: methods and description of a United Kingdom study linking occupational information held by employers to reproduction and child health - Maconochie, N; Doyle, P; Roman, E; Davies, G; Smith, P; Beral, V (1999)
Objectives - To describe the methods used in the nuclear industry family study for which a comprehensive database has been assembled that links employment in the nuclear industry and dosimetry records to information on employees' reproductive health and the health of their children. To discuss the response rates and characteristics of the study population. Methods - Occupational cohort design leading to a retrospective cohort study of reproductive outcomes reported by 46,396 current and former employees of both sexes in the nuclear industry. Employees of nuclear establishments in the United Kingdom operated by the Atomic Energy Authority, the Atomic Weapons Establishment, and British Nuclear Fuels were surveyed with postal questionnaires to collect information on pregnancies, children, and periods of infertility. Information on employment and monitoring for ionising radiation was supplied by the employing nuclear authority and was linked to pregnancies and periods of infertility with unique personal identification numbers. Results - The design and completion of this study resulted in high quality data on a representative population of the Atomic Energy Authority, Atomic Weapons Establishment, and British Nuclear Fuels workforces. The response to the survey was extremely good (82% for male workers and 88% for female workers, excluding undelivered questionnaires), and a unique relational database has been created which will enable infertility, pregnancy, and child health outcomes to be examined with respect to the employment and radiation monitoring characteristics of parents. Conclusion - This is the first United Kingdom study to link detailed reproductive history data to occupational information held by employers. The methods developed for the study were found to be feasible and successful. The design can be adapted for other investigations of reproductive hazards to men and women in the workplace and is currently in use to survey over 100,000 armed forces personnel in an investigation of reproductive outcome among veterans of the Gulf war.